Infestación natural de Lonchaeidae (Diptera) en variedades de melocotón - Montes, Sônia Maria N. M.; Raga, Adalton; Boliani, Aparecida C.; Strikis, Pedro C.; dos Santos, Pedro C. (My University, 2010)
The occurrence of Lonchaeidae was studied in peach fruit varieties on the rootstocks 'Okinawa' and Umê: Tropical, Ouromel 3, Jóia 4, Régis, Talismã, Aurora 2, Aurora 1, Dourado 2 and Doçura 2. Samples of 30 fruits were collected from each available plant in the Germplasm Bank located in Presidente Prudente, Brazil. A total of 633 specimens of Lonchaeidae were obtained with 394 from fruit varieties on 'Okinawa' and 239 on Umê. Captured species included Neosilba zadolicha, N. inesperata, N. pendula, N. certa, and Neosilba spp. (females). N. zadolicha and N. inesperata were observed in 77.78% of samples from the varieties on 'Okinawa'. On the Umê rootstock, the greatest incidence was of N. zadolicha, N. inesperata and N. pendula (55.6%, 33.3% and 33.3%). The varieties Ouromel 3, Talismã, Doçura 2 and Aurora 2 had the highest infestation rates by Lonchaeidae. N. certa had the lowest incidence and was only observed in the variety Doçura 2 on 'Okinawa'. Plants with more fruits showed a higher incidence of flies per fruit. Nevertheless, there was no significant correlation between fruit weight and fly number. No significant difference was observed in fruit weight and number of flies per fruit between the two rootstocks, 'Okinawa' and Umê. Peaches grown on 'Okinawa' and Umê rootstocks in the city of Presidente Prudente, are infested by Lonchaeidae species that present a preference for the different varieties, independent of fruit weight. This is a contribution to an understanding of the community of Lonchaeidae species, which provides a basis for their control.
Natural infestation of peach varieties by Lonchaeidae (Diptera)
Keywords: Fruit fly; Neosilba; Prunus persica; Tephritoidea